Pengembangan aliran sungai sebagai potensi Pembangkit Listrik Mikro Hidro serta edukasi dan akulturasi di Desa Meranti Tengah Dusun Batu Rangin Kecamatan Pintu Pohan Meranti Kabupaten Tobasa - Zufri Hasrudy Siregar; Roswani Siregar; Prinsi Rigitta; Nurdiana; Riana Puspita; Refiza; Masdania Zurairah; Indra Gunawan Purba; Jarnawi Hadi Saputra Tanjung (LPPM Universitas Al-Azhar medan, 2024)
Where rainwater is stored in the form of barrels, tubs, or ponds. Oil is as important as water for human life. Because the majority of Indonesians like fried food, cooking oil is still needed for household needs. Used cooking oil, oil produced from frying, is often used to save money, but its carcinogenic properties can cause cancer in the future. The purpose of this activity is to change the paradigm and change the paradigm of PTPN III Sei Mangke mothers. The results of this activity were 25 people, namely the age range of 28-37 years with a percentage of 36%, and the highest education level was high school with a percentage of 48% and there was a paradigm shift where previously they did not know until they understood based on the results of the questionnaire survey of the activity